Pola Pengajaran dan Pendidikan Warga Binaan Rumah Tahanan (RUTAN) Kelas II B Kabupaten Kolaka dengan adopsi Kurikulum Pondok Pesantren Al-Mawaddah Warrahmah - Muhammad Zakariah; Hartono Hartono; Kamaruddin Kamaruddin; Abdul Haris Nasution; Muhammad Askari Zakariah; Herry Muhammad Ramdhan (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Adoption of curriculum from Islamic boarding school was needed to build moral in prison. Curriculum were adopted from Islamic Boarding School Al-Mawaddah Warrahmah Kolaka. Islamic curriculum were consisted : Aqidah, Fiqih, Tafsir Al-Quran, Hadits, Akhlak, and Islamic history. Teaching method consisted practice, speech, giving question and getting answer. Monitoring and evaluating process were done by classified group learning (based on potency), final evaluation each six month. Obstacle were found a facility to learning. Concluded that model of teaching by adopted curriculum Islamic Boarding School showed enthusiastic of prison to learn a theology. Suggested to Commander a RUTAN Kelas II B Kolaka to be continued this program to future time.